Pemberdayaan Air Kelapa Menjadi Pupuk Tanaman Dalam Meningkatkan Pendapatan Masyarakat Pada UKM Pupuk Rahman Hayati - Muslih Muslih; Habib Akbar (Pusat Riset Manajemen dan Publikasi Ilmiah Serta Pengembangan Sumber Daya Manusia Sinergi Cendikia, 2022)
Pupuk Rahman Hayati is one of the UMKM that sells agricultural fertilizer services to farmers and provides fertilizer orders from small and large scale. Meet the needs of both plantation, maintenance and flower growers. Suggestions for the use of organic fertilizers or other materials are intended to reduce the current problems arising from the use of chemicals that have been proven to damage the soil and the environment. Such as the use of chemical fertilizers will result in damage to the soil. From its structure, there are currently circulating organic fertilizers in the form of solid and liquid organic fertilizers. Liquid organic fertilizer is a solution resulting from the decomposition of organic matter originating from plant residues, agro-industrial waste, animal waste, and human waste containing more than one nutrient.